Genomic Landscape of Head and Neck Squamous Cell Carcinoma Across Different Anatomic Sites in Chinese Population - Ju, Yunhe; Wu, Xingrao; Wang, Huizhen; Li, Bin; Long, Qing; Zhang, Dadong; Chen, Hao; Xiao, Nianqing; Li, Fugen; Zhang, Shiwen; Yang, Shenggang (Frontiers in Genetics, 2021)
Background: The characteristics of head and neck squamous cell carcinoma (HNSCC) across different anatomic sites in the Chinese population have not been studied. To determine the genomic abnormalities underlying HNSCC across different anatomic sites, the alterations of selected cancer-related genes were evaluated. Methods: Genomic DNA samples obtained from formalin-fixed, paraffin-embedded (FFPE) tissues were analyzed using targeted sequencing in a panel of 383 cancer-related genes to determine the genomic alterations. Results: A total of 317 FFPE HNSCC specimens were collected, and a total of 2,156 protein-coding mutations, including 1,864 single nucleotide variants and 292 insertions and deletions, were identified across more than six different anatomic sites. Mutation loads were distinct across the anatomic sites. Larynx carcinoma was found with the highest mutation loads, while nasopharynx carcinoma showed with the lowest mutation loads. A total of 1,110 gains and 775 losses were identified in the 317 specimens. Patients who had at least one clinically actionable alteration (levels 1–4 in OncoKB) were identified. One patient had an actionable alteration with level 1 evidence in OncoKB, TEX10-NTRK2 fusion, who may benefit from larotrectinib or entrectinib treatment. Conclusions: The genomic profiling of HNSCC using targeted sequencing can identify rational therapeutic candidate genes that are suitable for the treatment of the HNSCCs.